PENINGKATAN EFISIENSI PADA SISTEM PLTMH DENGAN CARA TURBIN HIBRID CROSSFLOW DAN PROPELLER HEAD 5 M - Paulus Sukusno (Politeknik Negeri Jakarta, 2021)
This study aims to increase the efficiency of the MHP (Micro Hydro Power Plant) system head 5 meter by means of the hybrid turbine (crossflow turbine and propeller turbine). Propeller turbines placed in the upper basin and crossflow turbines placed in water pipes exit (bottom). This research activity was carried out into three parts; The first is the MHP system with a propeller turbine. Both MHP system with crossflow turbines. The three MPH system hybrid turbine. The research results of the MHP system with a hybrid turbine can produce a maximum efficiency of 24.70%. The MHP system with propeller turbine can produce a maximum efficiency of 20.48%. The MHP system with a crossflow turbine can produce a maximum efficiency of 9.07%. So this research can prove that the efficiency of the MHP system with a hybrid turbine is better than using only a single turbine, but it is not always able to produce better electrical power.Keywords: Propeller, crossflow, hybrid, efficiency, electric power.